Analilis Intenfikasi Wajib Pajak Orang Pribadi Karyawan Dalam Upaya Meningkatan Penerimaan Pajak Penghasilan Pada KPP Pratama Bekasi Utara Tahun 2018 – 2020 - Mella Wati; Dwikora Harjo (Jurnal Ilmu Administrasi Publik, 2022)
The phenomenon in this study is that there is still a lack of knowledge on the intensification of individual taxpayers at KPP Pratama Bekasi Utara in fulfilling their tax obligations, seen from the results of the percentage realization of tax revenues in 2018 of 94.24%, and 2019 an increase of 101,  21%, and in 2020 entering the era of the covid-19 pandemic, the percentage of realized receipts decreased to 89.84%.   The purpose of this research is to find out and analyze the implementation of the intensification of individual employee taxpayers in an effort to increase income tax receipts at the KPP Pratama North Bekasi in 2018-2020.   The method of analysis uses qualitative.   The results of this study indicate that the Intensification of Individual Employee Taxpayers at KPP Pratama Bekasi Utara in 2018-2020 has not been fully in accordance with the procedures for intensification activities that have been set